2021
DOI: 10.1088/1361-665x/ac0398
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient structure design of bending stacking actuators based on IPMC with large output force

Abstract: Ionic electroactive polymers (iEAPs) are electroactive polymers that have been used as artificial muscles and have broad application potential. Although iEAPs show large bending deformation under low electric stimulus, the low output force significantly restricts their application. Based on an ionic polymer-metal composite (IPMC) actuator, we proposed a bending stacking structure principle which adapts the bending deformation cooperation conditions. According to the principle, the width stacking structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…and strong interface adhesion among cell components would be crucial factors to be considered for enhancing the blocking force. [58,102,103] The great advantages of ECAs can lead to realize potentially a wide range of future applications such as bionic robots, haptic systems, light weight low voltage braille displays, artificial muscles, low-voltage human-machine interfaces, autofocus camera modules, space and medical applications, etc. For example, owing to their flexibility, low driving voltage, moderate bending displacement, and operation in liquid or corrosive environments, various bionic robots have been successfully demonstrated based on the ECAs (e.g., imitation of fins, limbs, joints, and trunks, flowers etc.).…”
Section: Summary and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…and strong interface adhesion among cell components would be crucial factors to be considered for enhancing the blocking force. [58,102,103] The great advantages of ECAs can lead to realize potentially a wide range of future applications such as bionic robots, haptic systems, light weight low voltage braille displays, artificial muscles, low-voltage human-machine interfaces, autofocus camera modules, space and medical applications, etc. For example, owing to their flexibility, low driving voltage, moderate bending displacement, and operation in liquid or corrosive environments, various bionic robots have been successfully demonstrated based on the ECAs (e.g., imitation of fins, limbs, joints, and trunks, flowers etc.).…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…and strong interface adhesion among cell components would be crucial factors to be considered for enhancing the blocking force. [ 58,102,103 ]…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…As a new smart material, artificial muscle has attracted people's research interest because of its complex transformation of electrical energy, mechanical energy and chemical energy, which has a wide application prospect in the fields of bionic bioengineering, medical engineering and robot [3,4]. Ionic polymer metal composite (IPMC) is an ideal artificial muscle material because of its light weight, good flexibility, low actuation voltage and good biocompatibility [5][6][7]. In the course of the study, people found that conventional Nafion-based IPMC actuators have two disadvantages: (a) Poor durability in air because of the leakage of the internal electricity and hydrated actions through cracks in the metallic electronics [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…With both simulation and experiment, we demonstrated that IPMC with a super simple macroscopic serrated interface can achieve high-performance electro-active displacement, suggesting a minimal design strategy for the ionic electroactive polymer (EAP) for future reference. Furthermore, anisotropic actuation will open up further possibilities for the following versatile deformation design through stacking [33] or an asynchronous array [34].…”
Section: Introductionmentioning
confidence: 99%